ANALYSIS OF TOURISM SUITABILITY AS THE BASIS FOR COASTAL ENVIRONMENT MANAGEMENT AT BLEBAK BEACH, JEPARA REGENCY - Muhammad Chairul Umam; Frida Purwanti; Churun Ain (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2026)
The increasing utilization of coastal tourism requires an integrated assessment of area suitability that combines biophysical characteristics and water quality. This study aims to evaluate the suitability of Blebak Beach for tourism using the Tourism Suitability Index (TSI) and to determine water quality status through the STORET method as a basis for sustainable management. The study was conducted at 2 stations during April–July 2025. The TSI was calculated based on coastal and water biophysical parameters, including beach width and slope, depth, current velocity, water clarity, freshwater availability, and the presence of hazardous biota. Water quality was analyzed using physical, chemical, and microbiological parameters, and results were compared with coastal water quality standards. Results showed an IKW score of 2.210 (suitable) at Station 1 and 2.690 (highly suitable) at Station 2, indicating the area’s spatial and functional suitability for recreational activities. Conversely, water quality was classified as moderately polluted, with a score of -22 at both stations, due to nitrate and phosphate concentrations exceeding quality standards, which are attributed to aquaculture pond runoff, particularly uneaten feed and metabolic waste. Integration of both approaches is necessary to ensure sustainable coastal tourism management through nutrient input control and periodic water quality monitoring. Zoning of aquaculture ponds and tourism zones is implemented to reduce direct interaction between pollution sources and recreational areas.